Evolution of treatment strategies for oligometastatic NSCLC patients – A systematic review of the literature. (November 2019) - Schanne, Daniel H.; Heitmann, Jana; Guckenberger, Matthias; Andratschke, Nicolaus H.J.
Highlights: No uniform definition exists on the number of metastases which qualify for inclusion as OMD. Discrepancy between pre-specified number of metastases and number actually treated. Surgery most commonly used LAT strategy with increasing use of SBRT after 2011. No survival differences were detectable between locally-ablative treatments. Time trend showing improved overall survival of oligometastatic patients after 2011. Abstract: Background: The concept of oligometastatic disease (OMD) has expanded the scope of potentially curative therapy for metastatic NSCLC. However, large uncertainties remain regarding its definition and optimal management strategies. We therefore conducted a systematic review to investigate the value of various multimodality treatment concepts. Methods: We searched the available literature in Pubmed, Medline and EMBASE using the terms "oligomet*", "synchron*", "oligorec*", "metachr*" "NSCLC", "lung cancer" and "stage IV" and included studies reporting treatment regimens and outcomes on radically treated patients with either "synchronous", "metachronous" or "mixed" OMD. Only de-novo diagnosis of OMD was considered. The impact of patient and treatment characteristics on overall survival (OS) and time trends in patterns of care were investigated. Results: 54 studies published between 1987 and 2018 were included. Despite a wide range of OMD definitions, 90.1% of patients were treated for a single metastasis. Systemic therapy was used as backbone treatment for most patients. Although surgery was the preferred local treatment in earlier studies, the use of stereotactic radiotherapy increased rapidly after 2011. No OS difference was observed between surgery or radiotherapy as the treatment of primary tumor or metastases, respectively. A time trend towards improved OS after 2011 could be detected. Conclusions: While evidence in favor of radical treatment is emerging, most studies remain retrospective and mainly evaluate patients with singular metastases. While surgery, stereotactic radiotherapy and chemotherapy are the cornerstones of current treatment strategies, future clinical trials need to address the high risk of distant metastases by integrating targeted or immunotherapy.